2020
DOI: 10.1186/s13287-020-02019-5
|View full text |Cite|
|
Sign up to set email alerts
|

Definitive hematopoietic stem/progenitor cells from human embryonic stem cells through serum/feeder-free organoid-induced differentiation

Abstract: Background Ex vivo production of hematopoietic stem/precursor cells (HSPCs) represents a promising versatile approach for blood disorders. Methods To derive definitive HSPCs from human embryonic stem cells (ESCs), we differentiated mesodermally specified embryoid bodies (EBs) on gelatin-coated plates in serum/feeder-free conditions. Results Seven-day EB maturation followed by an 8-day differentiation period on OP9 cells provided the highest number of definitive (CD34+ CD235a−, 69%, p < 0.01) and lowest nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In comparison with the other types of vascular endothelial cells, CD34 is a quite specific marker for hemogenic endothelium and CD31 is a general marker for all [ 30 ]. In vitro differentiation experiments concluded that CD43 defined definitive hematopoietic stem/progenitor cells from human embryonic stem cells [ 31 , 32 ]. Unlike the SCL-S, all the CD31, CD34, and CD43 markers were still not observed on the endothelial layer of E9.5 aorta ( Figure 4 A), instead, dispersed CD31 + /CD34 + /CD43 + cells were found in the vessel cavities ( Figure 4 A,B) and weak but significant c-Kit and CD45 markers were revealed on most of these cells ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the other types of vascular endothelial cells, CD34 is a quite specific marker for hemogenic endothelium and CD31 is a general marker for all [ 30 ]. In vitro differentiation experiments concluded that CD43 defined definitive hematopoietic stem/progenitor cells from human embryonic stem cells [ 31 , 32 ]. Unlike the SCL-S, all the CD31, CD34, and CD43 markers were still not observed on the endothelial layer of E9.5 aorta ( Figure 4 A), instead, dispersed CD31 + /CD34 + /CD43 + cells were found in the vessel cavities ( Figure 4 A,B) and weak but significant c-Kit and CD45 markers were revealed on most of these cells ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…hPSCs, such as hESCs, are ideal seed cells for obtaining large numbers of HSPCs and for scalable manufacturing of human hematopoietic or BM organoids. Accumulating evidence demonstrates that hESCs can differentiate into HSPCs and multilineage blood cells [ 36 , 37 ]. Therefore, we used a stepwise induction protocol to generate human CD34 + HSPCs from hESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Branchways are key structures for air conduction in the lungs. However, lung organoids are typically spherical and cannot fully simulate this morphological structure [75]. In addition to epithelial cells, many other cell types are involved in the pulmonary microenvironment.…”
Section: Cluster 3 (Fig 5a Orange Cluster): Cystic Brosis (Cf)mentioning
confidence: 99%